Demographically Corrected Norms for African Americans and Caucasians on the Hopkins Verbal Learning Test-Revised, Brief Visuospatial Memory Test-Revised, Stroop Color and Word Test, and Wisconsin Card Sorting Test 64-Card Version - Norman, Marc A. (2011)
Memory and executive functioning are two important components of clinical neuropsychological (NP) practice and research. Multiple demographic factors are known to affect performance differentially on most NP tests, but adequate normative corrections, inclusive of race/ethnicity, are not available for many widely used instruments. This study compared demographic contributions for widely used tests of verbal and visual learning and memory (Brief Visual Memory Test-Revised, Hopkins Verbal Memory Test-Revised), and executive functioning (Stroop Color and Word Test, Wisconsin Card Sorting Test-64) in groups of healthy Caucasians (n = 143) and African-Americans (n = 103). Demographic factors of age, education, gender, and race/ethnicity were found to be significant factors on some indices of all four tests. The magnitude of demographic contributions (especially age) was greater for African-Americans than Caucasians on most measures. New, demographically corrected T-score formulas were calculated for each race/ethnicity. The rates of NP impairment using previously published normative standards significantly overestimated NP impairment in African-Americans. Utilizing the new demographic corrections developed and presented herein, NP impairment rates were comparable between the two race/ethnicities and unrelated to the other demographic characteristics (age, education, gender) in either race/ethnicity group. Findings support the need to consider extended demographic contributions to neuropsychological test performance in clinical and research settings.